Exposure of female NZBWF1 mice to imiquimod-induced lupus nephritis at an early age via a unique mechanism that differed from spontaneous onset. (2nd February 2022) - Hayakawa, Kunihiro; Fujishiro, Maki; Yoshida, Yuko; Kataoka, Yuko; Sakuma, Shota; Nishi, Takuya; Ikeda, Keigo; Morimoto, Shinji; Takamori, Kenji; Sekigawa, Iwao
Abstract: Systemic lupus erythematosus (SLE) is a chronic inflammatory and representative autoimmune disease. Extremely complicated and multifactorial interactions between various genetic factors and individual susceptibility to environmental factors are involved in the pathogenesis of SLE. Several studies have reported that mutation and activation of toll-like receptor (TLR) 7 are involved in the onset of autoimmunity, including SLE. Thus, we investigated the response of SLE-prone mice to continuous environmental factors, particularly TLR7 agonist exposure, and changes in their phenotypes. Female and male NZBWF1 (BWF1) mice were treated from 20 weeks of age with a TLR7 agonist, imiquimod (IMQ), 3 times weekly for up to 12 weeks. IMQ-exposed female BWF1 mice showed worsened lupus nephritis. However, autoantibody production was not enhanced in IMQ-exposed female BWF1 mice. The Th1 cytokine expression was upregulated in the kidney of IMQ-treated mice. In IMQ-exposed BWF1 mice, neutralization of IFN-γ suppressed early-phase lupus nephritis. Additionally, in male BWF1 mice IMQ exposure induced minor aggravation of lupus nephritis. These results suggest that the induction of aggravated lupus nephritis by TLR7 agonist exposure was related to the expression of IFN-γ via acute TLR7 signal-induced renal inflammation, and that the involvement of genetic factors associated with a predisposition to SLE is also essential. Thus, the activation of TLR7 signaling by exposure to environmental factors may upset the balance of factors that maintain SLE remission. We hypothesize that the inhibition of TLR7 signaling and IFN-γ signaling is effective for preventing the onset and flare and maintaining remission of lupus nephritis. Abstract : We examined the phenotypes of imiquimod-induced SLE in female NZBWF1 mice. IFN-? signaling was involved in the early phase of development of imiquimod-induced lupus nephritis. However, in the later phase, IFN-? signaling no longer played a critical role. Graphical Abstract: